Ω phase strengthened 1.2GPa metastable β titanium alloy with high ductility. (15th March 2019) - Gao, Junheng; Knowles, Alexander J.; Guan, Dikai; Rainforth, W. Mark
Abstract: This paper provides a novel approach for exploiting ω phase strengthening in a metastable β titanium alloy while retaining high ductility. The addition of 1 wt% Fe into our previously designed Ti-7Mo-3Cr alloy can efficiently control the growth of ω phase following air-cooling, resulting in a ultrahigh yield strength ( R p 0.2 of 1210 MPa) with large ductility (εf of 0.15). Microstructural analysis of deformed alloys showed that the growth of ω phase in the air-cooled Ti-7Mo-3Cr-1Fe alloy modified the deformation mechanism from 332 twinning and dislocation slip, in the water-quenched alloy, to localized dislocation plasticity in ω-void channels. Graphical abstract: Stress-strain curves of both air-cooled and water-quenched Ti-7Mo-3Cr-1Fe and Ti-7Mo-3Cr alloy and their corresponding dark-field images showing the distribution of omega phase with different sizes; insets are their corresponding select-area electron diffraction patterns. (a) Air-cooled Ti-7Mo-3Cr-1Fe alloy, (b) water-quenched Ti-7Mo-3Cr-1Fe alloy, (c) air-cooled Ti-7Mo-3Cr alloy and (d) water-quenched Ti-7Mo-3Cr alloy. Unlabelled Image